2015
DOI: 10.1590/s1980-57642015dn91000010
|View full text |Cite
|
Sign up to set email alerts
|

Patients with dementia syndrome in public and private services in southern Brazil

Abstract: Dementia is characterized by deficits in more than one cognitive domain, affecting language, praxis, gnosis, memory or executive functions. Despite the essential economic growth observed in many developing countries, especially over the last century, huge differences remain in health care, whether among nations themselves or across different regions of the same country.ObjectiveThe aim of this study was to assess the management and main features of dementia, comparing public (PUBL) and private (PRIV) reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“… 14 , 16 Another possible explanation for the absence of studies in low-income countries may be related to the limited access to health services, as well as the limited creation and implementation of public health policies that contribute toward both patient diagnosis and treatment. 14 , 15 , 17 …”
Section: Discussionmentioning
confidence: 99%
“… 14 , 16 Another possible explanation for the absence of studies in low-income countries may be related to the limited access to health services, as well as the limited creation and implementation of public health policies that contribute toward both patient diagnosis and treatment. 14 , 15 , 17 …”
Section: Discussionmentioning
confidence: 99%
“…In tertiary centers-based studies, the frequency of these two etiologies ranged from 3.7% to 15% of cases [9][10][11][12][13] Similarly, a study based on neuropathological diagnosis cases 14 showed that LBD caused 15% of cases of dementia, whether isolated or associated with other pathologies. LBD was also the second most frequent neurodegenerative etiology of dementia and related to a higher risk of dementia with an odds ratio (OR) of 3.4 (CI: 1.94-5.97).…”
Section: Epidemiologymentioning
confidence: 99%
“…A DDP representa 13,5% dos casos de parkinsonismo com demência 6 , enquanto a DCL é responsável por menos de 5% das etiologias 7,8 . Em estudos baseados nas casuísticas de centros terciários, a prevalência dessas duas etiologias varia entre 3,7 a 15% [9][10][11][12][13] dos casos de demência. Esses dados são similares aos observados em estudo neuropatológico prévio, em que a DCL foi responsável por 15% das etiologias de demência, seja de forma isolada ou associada a outras patologias 14 .…”
Section: Epidemiologiaunclassified